Students’ attendance at management accounting classes – reasons and the effect on academic performance / Rosiatimah Mohd Isa and Azrul Abdullah - Mohd Isa, Rosiatimah; Abdullah, Azrul (Research Management Institute (RMI), 2009)
This study explores the reasons for non-attendance and what motivates those who attend management accounting classes at undergraduate level of the accounting program and investigate the impact of attendance upon academic performance on the course. The subjects of the research were students in three undergraduate programs of Accountancy Faculty at UiTM Perlis namely Diploma in Accountancy, Diploma in Accounting and Information System and Bachelor of Accountancy who took the highest level of management accounting courses at their respective programs. The total number of students involved was 121 students. A short questionnaire and class attendance records were used for this survey. The highest mean score cited for the reasons students attending management accounting class was ‘to learn, to understand, and to increase their knowledge on the course’. Students’ preoccupation with assignments and study for other tests, and genuine health reasons were ranked highly for reasons non-attendance reasons. A clear positive relationship between attendance and academic performance was evident.